Hospital-Acquired Methicillin-Resistant Staphylococcus aureus Bloodstream Infections in Québec: Impact of Guidelines. (5th June 2017) - Li, Lynne; Fortin, Elise; Tremblay, Claude; Ngenda-Muadi, Muleka; Garenc, Christophe; Moisan, Danielle; Villeneuve, Jasmin; Quach, Caroline
Abstract : OBJECTIVE: We examined the impact of methicillin-resistant Staphylococcus aureus (MRSA) guidelines in Québec adult hospitals from January 1, 2006, to March 31, 2015, by examining the incidence rate reduction (IRR) in healthcare-associated MRSA bloodstream infections (HA-MRSA), using central-line associated bloodstream infections (CLABSIs) as a comparator. METHODS: In this study, we utilized a quasi-experimental design with Poisson segmented regression to model HA-MRSA and CLABSI incidence for successive 4-week surveillance segments, stratified by teaching status. We used 3 distinct periods with 2 break points (April 1, 2007, and January 3, 2010) corresponding to major MRSA guideline publications and updates. RESULTS: Over the study period, HA-MRSA incidence decreased significantly in adult teaching facilities but not in nonteaching facilities. Prior to MRSA guideline publication (2006–2007), HA-MRSA incidence decrease was not significant ( P =.89), while CLABSI incidence decreased by 4% per 4-week period ( P =.05). After the publication of guidelines (2007–2009), HA-MRSA incidence decreased significantly by 1% ( P =.04), while no significant decrease in CLABSI incidence was observed ( P =.75). HA-MRSA and CLABSI decreases were both significant at 1% for 2010–2015 ( P <.001 and P =.01, respectively). These decreases were gradual rather than sudden; break points were not significant. Teaching facilities drove these decreases. CONCLUSION: During the study period, HA-MRSA and CLABSI rates decreased significantly. In 2007–2009, the significant decrease in HA-MRSA rates with stable CLABSI rates suggests an impact from MRSA-specific guidelines. In 2010–2015, significant and equal IRRs for HA-MRSA and CLABSI may be due to the continuing impact of MRSA guidelines, to the impact of new interventions targeting device-associated infections in general by the 2010–2015 Action Plan, or to a combination of factors. Infect Control Hosp Epidemiol 2017;38:840–847